Zosterops lateralis subsp. tropica Mees - , Mary (Zenodo, 2011)
Zosterops lateralis tropica Mees Zosterops lateralis tropica Mees, 1969: 100 (Espiritu Santo). Now Zosterops lateralis tropicus Mees, 1969. See Mees, 1969: 100–102, Bregulla, 1992: 252, Dickinson, 2003: 629, and van Balen, 2008: 467–468. HOLOTYPE: AMNH 214054 , adult male, collected on Espiritu Santo Island, 15.15S, 166.50E (USBGN, 1974), Vanuatu, on 1 September 1926, by Rollo H. Beck on the Whitney South Sea Expedition (no. 22507). COMMENTS: Mees gave the AMNH number of the holotype in the original description and the range of tropica as ‘‘the northern New Hebrides: Malo, Espiritu Santo, Tongoa (off Espiritu Santo, not to be confused with Tongoa near Epi); Banks Group: Gaua, Melapav, Ureparapara or Blight (sic); Torres Group: Low Island, Toga. ’’ Specimens other than the holotype that Mees examined from those islands are paratypes of tropica . Mees visited AMNH when working on this part of his Zosteropidae monograph and would have seen all of the specimens in the AMNH collection. Paratypes in AMNH are: Malo, males, AMNH 213597 , 213598 Espiritu Santo, males, AMNH 214050–214053 , female, AMNH 214065 , juvenile sex?, AMNH 215883 Gaua, male, AMNH 214056 Melapav, female, AMNH 214064 Bligh, male, AMNH 216128 Low, males, AMNH 216115– 216118 , 216120 , females, AMNH 216121 , 216122 , 216124 , 216125 Toga, male, AMNH 216126 , female, AMNH 216127 . AMNH 216119 and AMNH 216123 had already been exchanged to NRM and CM, respectively, and would not have been seen at AMNH by Mees. AMNH 216116 had been exchanged to Rothschild and renumbered AMNH 459013 when that collection came to AMNH in 1932; it would have been part of Mees’ type series. Bregulla (1992: 252) listed Tanna and Aniwa birds as Z. l. tropicus without comment. The holotype of this taxon had not previously been included in the type collection at AMNH. : Published as part of Mary, 2011, Type Specimens Of Birds In The American Museum Of Natural History Part 9. Passeriformes: Zosteropidae And Meliphagidae, pp. 1-193 in Bulletin of the American Museum of Natural History 2011 (348) on page 32 : {"references": ["Mees, G. F. 1969. A systematic review of the Indo- Australian Zosteropidae (Part III). Zoologische Verhandelingen 102: 3 - 390.", "Bregulla, H. L. 1992. Birds of Vanuatu. Oswestry, Shropshire, England: Anthony Nelson, 294 pp.", "Dickinson, E. C. (editor). 2003. The Howard and Moore complete checklist of the birds of the world. 3 rd ed. London: Christopher Helm, 1039 pp.", "van Balen, S. 2008. Family Zosteropidae (whiteeyes). In J. del Hoyo, A. Elliot, and D. Christie (editors), Handbook of birds of the world, vol. 13, Penduline-tits to shrikes: 402 - 485. Barcelona: Lynx Edicions, 879 pp., 60 pls., 536 photographs."]}